Tuning stoichiometry of high‐entropy oxides for tailorable thermal expansion coefficients and low thermal conductivity. Issue 2 (17th October 2021) - Xu, Liang; Su, Lei; Wang, Hongjie; Gao, Hongfei; Lu, De; Peng, Kang; Niu, Min; Cai, Zhixin
Abstract: Thermal barrier coating materials with proper thermal expansion coefficient (TEC), low thermal conductivity, and good high‐temperature stability are of great significance for their applications in next‐generation turbine engines. Herein, we report a new class of high‐entropy (La0.2 Sm0.2 Er0.2 Yb0.2 Y0.2 )2 Cex O3+2x with different Ce 4+ contents synthesized by a solid‐state reaction method. They exhibit different crystal structures at different Ce 4+ content, including a bixbyite single phase without Ce 4+ doping ( x = 0), bixbyite‐fluorite dual‐phase in the RE2 O3 ‐rich region (0 < x < 2), and fluorite single phase in the stoichiometric ( x = 2) and CeO2 ‐rich region ( x > 2). The high‐entropy (La0.2 Sm0.2 Er0.2 Yb0.2 Y0.2 )2 Ce x O3+2 x exhibit tailorable TECs at a large range of 9.04 × 10 –6 –13.12 × 10 –6 °C –1 and engineered low thermal conductivity of 1.79–2.63 W·m –1 ·K –1 . They also possess good sintering resistance and high‐temperature phase stability. These results reveal that the high‐entropy (La0.2 Sm0.2 Er0.2 Yb0.2 Y0.2 )2 Cex O3+2x are promising candidates for thermal barrier coating materials as well as thermally insulating materials and refractories.